Tillsyn av djur på bete : betydelsen av lockgiva och regelbundna tider - Petersson, Linda (SLU/Dept. of Animal Environment and Health (until 231231), 2006)
During natural conditions cattle live in large herds, which are divided into subgroups of 10-15 animals. Humans have held cattle for over 9000 years. Today we mostly have cows for milk and meat production during more or less intensive forms. Most of the Swedish cattle have the opportunity to graze during the summer time. This partly arises from the Swedish Animal Protection law which stipulates that cattle must have the option to be outside and graze, also partly because it makes it easier for the farmer. During this period the animals has to have sufficient supervision everyday. This is to ensure that the cattle don't have any injuries. The supervision can take a long time if the farmer is unable to locate all of his/her cattle, for instance if they would escape. Most people agree that if we should rear animals then we should also protect them from unnecessary suffering, which makes good supervision a necessary requirement. Many studies have shown that cows can differentiate between people that treat them kind and gentle and those that are aversive towards them. It has also been shown that animals which have been treated in a kinder manner are easier to handle and produce more. With different learning techniques you can teach cows to do different tasks for a reinforcement.